2006
DOI: 10.1080/02791072.2006.10400586
|View full text |Cite
|
Sign up to set email alerts
|

Relating Substance Abuse Counselor Background to the Provision of Clinical Tasks

Abstract: This study examines the diverse academic and professional background characteristics of substance abuse treatment counselors, relating these characteristics to the work counselors are doing. Results indicate that while academic and professional background characteristics differentiate whether counselors perform certain clinical tasks or not, they do not differentiate the amount of time they spend doing them. In fact, regression analyses indicate that academic and professional background characteristics current… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…While the studies thus far presented in this paper are outdated, there are two recent quantitative studies that examine provision of clinical tasks distributed among recovering and non-recovering counsellors [24] and the determinants of intrinsic job motivation [25].…”
Section: Introductionmentioning
confidence: 99%
“…While the studies thus far presented in this paper are outdated, there are two recent quantitative studies that examine provision of clinical tasks distributed among recovering and non-recovering counsellors [24] and the determinants of intrinsic job motivation [25].…”
Section: Introductionmentioning
confidence: 99%
“…Much of the literature that has investigated recovered addicts working in the addiction field began to accumulate in the 1970s, and 1980s, but began to diminish in the 1990s, with only one study being reported in the twenty-first century (Knudsen et al, 2006). Among these studies, however, there were only two in my review of the literature that explored the topic of the potential for relapse among recovered counselors working in the field of addiction (Kinney, 1983;McGovern & Armstrong, 1987), with only one involving a qualitative approach (McGovern & Armstrong, 1987).…”
Section: Resultsmentioning
confidence: 99%
“…While the studies thus far presented in this paper are outdated, there are two recent studies that examine provision of clinical tasks distributed among recovered and non-recovered counselors (Knudsen, Gallon, & Gabriel, 2006) and the determinants of intrinsic job motivation (Tinney & Roberts, 2002).…”
Section: Literature Reviewmentioning
confidence: 96%